Hate speech recognition in multilingual text: hinglish documents - Yadav, Arun Kumar; Kumar, Mohit; Kumar, Abhishek; Shivani; Kusum; Yadav, Divakar (International journal of information technology (Singapore. Online), 2023)
The Internet is a boon for mankind but its misuse has been increasing drastically. Social networking platforms such as Facebook, Twitter and Instagram play a predominant role in expressing views by the users. Sometimes users wield abusive or inflammatory language, that may provoke readers. This paper aims to evaluate various machine learning and deep learning techniques to detect hate speech on various social media platforms in the Hinglish (English-Hindi code-mix) language. In this paper, we apply and evaluate several machine learning and deep learning methods, along with various feature extraction and word-embedding techniques, on a consolidated dataset of 20600 instances, for hate speech detection from tweets and comments in Hinglish. The experimental results reveal that deep learning models perform better than machine learning models in general. Among the deep learning models, the CNN-BiLSTM model with word2vec word embedding provides the best results. The model yields 0.876 accuracy, 0.830 precision, 0.840 recall and 0.835 F1-score. These results surpass the recent state-of-art approaches.